The effects of zeranol on male genital tract in merino lambs - Sadettin TIPIRDAMAZ; Ahmet ACET; Ramazan KADAK; Hasan ERDEN (Eurasian Journal of Veterinary Sciences)
In this study, fourty-fiVe merino lambs were used. These animals were divided into there groups. Twelve mg of Zeranol were implanted sulbcutaneously to ear of the first and second groups lambs. Fourty days later, the same dose of Zeranol was reimplanted to the second, group lamlbs. The remaining 15 lambs were served as nonimplanted controls. Five lambs belonging to each group were slaughtered at 80, 1/20 and 160 days after implantation. Before slaughtering the lambs body weight were measured. Then testes, epididymides, vesicular glands and bulbourethral glands were weighted.